2015
DOI: 10.15547/bjvm.859
|View full text |Cite
|
Sign up to set email alerts
|

Histological and immunohistochemical changes of the thyroid gland during the foetal and postnatal period of development in indigenous Large White crossbred pigs

Abstract: The present study was carried out to ascertain the morphometric, histological and immunohistochemical changes (expression of calcitonin and somatostatin) in the thyroid gland of indigenous local pig crosses during the foetal and postnatal period of development. A total of thirty foetal thyroids (40) grouped into early and late foetal period, fifteeen (15) prepubertal and ten (10) pubertal thyroids obtained from slaughtered pigs in the local abattoir were used. Histomorphometrically, all the measured parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…The current study observed that the tissue lining the follicles is simple cuboidal epithelial tissue, which is composed of cuboidal cells with a central spherical nucleus, and high and low simple cuboidal epithelial tissue. This is consistent with the study of the gland in wild African grusscutter [10], local female donkeys [15], local Iraqi sheep [16], white hybrid pigs [25], and other studies. When the follicle consists of high simple cuboidal epithelial tissue, the gland is hyperactive, but in the case of low cubic epithelial tissue, the gland is underactive, as the type of tissue is an indicator of the gland's activity and its functional state.…”
Section: Discussionsupporting
confidence: 93%
“…The current study observed that the tissue lining the follicles is simple cuboidal epithelial tissue, which is composed of cuboidal cells with a central spherical nucleus, and high and low simple cuboidal epithelial tissue. This is consistent with the study of the gland in wild African grusscutter [10], local female donkeys [15], local Iraqi sheep [16], white hybrid pigs [25], and other studies. When the follicle consists of high simple cuboidal epithelial tissue, the gland is hyperactive, but in the case of low cubic epithelial tissue, the gland is underactive, as the type of tissue is an indicator of the gland's activity and its functional state.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with the study of the thyroid gland in Iraqi buffalo [8], gazelles and sheeps [26], guinea pigs (Guniea pigs), and albino rats [17]. On the other hand, the results of this study regarding the capsule for both animals did not agree with the findings of the study of the thyroid gland in the African giant rat [27] and white hybrid pigs [25], where it was found that the capsule is consist of a single layer of connective tissue. Furthermore, it did not agree with the study on black Bengal goat thyroid gland [28] and rabbits [29], as the capsule was found to be composed of three layers: inner layers and outer layer consisting of connective tissue and middle layer consisting of fatty and nervous tissue.…”
Section: Discussionsupporting
confidence: 79%
“…While these results differed with the study of [24] on Belarusian hedgehog, in which the size of the right lobe is similar to the size of the left lobe. The reason for the difference in size is may due to the difference in age, sex, as well as the activity of the animal depending on the functional need [13], [25]. In contrast, the color of the gland is similar to what was found in the previously mentioned studies.…”
Section: Discussionmentioning
confidence: 56%